(untitled) (European Journal of Pedagogical Initiatives and Educational Practices, 2025)
This article discusses several methods that help primary school students improve their ability to master simple geometric shapes and formulas using tables. The research work presents a step-by-step approach to calculating the perimeter and area of rectangles, triangles, polygons, as well as the surface area and volume of simple spatial shapes such as cubes, parallelepipeds, and prisms. The presented methods are important in developing students’ logical thinking skills and developing the ability to systematically solve complex problems in the imagination.